A pilot study on the knowledge and attitude toward the new American Heart Association (AHA) cardiopulmonary resuscitation 2010 guideline on "C-A-B" sequence and the correlation with the willingness to perform bystander CPR among health personnel in Emergency Department, Hospital Sains Malaysia (HUSM) - Deraman@Ismail, Norwani (2015)
Introduction: Cardiopulmonary resuscitation, carried out in an integrated and coordinated series of actions known as chain of survival is an important element in cardiac arrest case. The presence of bystander CPR to initiate basic life support before arrival of EMS in out of hospital cardiac arrest is not promising in our local setting, even in Malaysia. Deterrence in doing resuscitation process might be due to various reasons, including mouth to mouth ventilation. Thus, this study focuses on the impact of the latest CAB sequence with the willingness to do bystander CPR. Objectives: 1) To compare the knowledge and attitude between health personnel in EDHUSM. 2) To determine the association between the CPR sequence and the willingness to do bystander CPR. 3) To determine the associated factors contribute to the willingness of bystander CPR Methods: This is a cross-sectional study using the modified questionnaire survey form to achieve all the objectives. The questionnaire form was distributed among the health personnel in EDHUSM. All health personnel in EDHUSM who fulfilled the inclusion criteria had been enrolled in this study. This survey was done from November 2013 to March 2014. Results: Out of 96 participants surveyed, all of them completed the questionnaire form making the response rate of 100 %. There were imbalances between the knowledge and attitude between the groups of health personnel. Comparing between the groups, medical officer had more knowledge on basic life support and it reflected on the confidence level upon encounter cardiac arrest case. Although majority of participants agreed that rescue breathing were the deterrence step and acronym CAB was more practical for the bystander CPR outside hospital, but study has shown that no significant difference between preferred CPR sequence and the willingness to do bystander CPR with the fisher exact test (p value of 0.554). It might not be reflected true outside population because the participants were those who had already involve in resuscitation process daily. They know the importance of bystander CPR, either CAB or ABC sequence will not alter the decision to be bystander CPR. The only significant factor determine the willingness to do bystander was year of service (p value of 0.049) Conclusion: People are aware of the importance of bystander CPR during cardiac arrest. Majority of participants preferred the CAB sequence but their willingness to do bystander CPR is not related with the chosen CPR sequence.